2017
DOI: 10.1121/1.5009451
|View full text |Cite
|
Sign up to set email alerts
|

The spatial coherence of noise fields evoked by continuous source distributions

Abstract: In this work, analytic expressions for the spatial coherence of noise fields are derived in the modal domain with the aim of providing a sparse representation. For this purpose, the sound field in a region of interest is expressed in terms of a given pressure distribution on a virtual surrounding cylindrical or spherical surface. According to the Huygens-Fresnel principle, the sound pressure on this surface is represented by a continuous distribution of elementary line or point sources, where orthogonal basis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…In a given loudspeaker setup, substituting (24) into (9), the representation of secondary noise field coefficients can be rewritten by…”
Section: Noise Control In the Subspacementioning
confidence: 99%
See 1 more Smart Citation
“…In a given loudspeaker setup, substituting (24) into (9), the representation of secondary noise field coefficients can be rewritten by…”
Section: Noise Control In the Subspacementioning
confidence: 99%
“…For spatial ANC performance estimation over an entire region, Chen et al investigated ANC performance by noise pattern analysis of the primary noise field [22,23]. Buerger et al investigated the coherence between two observation points in the noise field evoked by given continuous source distributions, which can be applied to predict the upper bound of ANC performance in the region of interest [24]. However, the capability of secondary sources, in particular room environments, has not yet been explored.…”
Section: Introductionmentioning
confidence: 99%
“…Buerger et al investigated the coherence between two observation points in the noise field evoked by given continuous source distributions, which can be applied to predict the upper bound of the ANC performance. 15 Kuo and Morgan investigated the relation between the minimum residual error and the coherence between the reference microphone and the error microphone, 16 which provided the solution in the single channel ANC systems. Bitzer et al found that the complex coherence function of the noise field for all sensors is a valuable tool to examine the theoretical limits of NR for speech recognition.…”
mentioning
confidence: 99%